Voices of Youth in Post-Conflict Burundi : Perspectives on Exclusion, Gender, and Conflict - World Bank (Washington, DC, 2013)
This report examines youth in post-conflict Burundi. The research responds to the nascent but growing body of knowledge on conflict, young men and gender. War and violence have devastated societies and economies throughout Africa with young men being the main perpetrators of this violence. This research attempts to contribute to this body of knowledge. It looks at youth and young men in particular in two countries emerging from years of ethnic conflict, with a view to identifying if gender norms may increase the risk of renewed conflict. Specific objectives of the research in Burundi were to examine how poor and excluded youth are faring and coping in the country's post-conflict environment; how gender dynamics are playing out in Burundian society and how these may contribute to increased risk of renewed conflict; and what the implications of findings are in terms of future policy and programming. The study takes a special look at youth ex-combatants who are in the process of being reintegrated back into their communities, given that this group has been a focus of a high profile demobilization and reintegration program in Burundi and given that ex-combatants are considered to represent a higher risk to renewed fighting. The report is organized as follows. After this introductory chapter, chapter two presents the context for the study, and includes a definition of youth as well as a brief description of the country context and socioeconomic indicators for youth. Chapter three presents the main research findings on how youth are faring, how they see their prospects, and the challenges they face, including those related to meeting gender norms and other social institutions. Chapter four presents a description of the policy response and programs targeting youth, scanty as they may be. Lastly, chapter five summarizes the study's main findings and conclusions, and presents an overall approach for youth development as well as policy directions.